Design-in-play: improving the variability of indoor pervasive games - Guo, Bin; Fujimura, Ryota; Zhang, Daqing; Imai, Michita (Multimedia tools and applications, 2012)
Treasure is a pervasive game playing in the context of people’s daily living environments. Unlike previous pervasive games that are based on the predefined contents and proprietary devices, Treasure exploits the “design-in-play” concept to enhance the variability of a game in mixed-reality environments. Dynamic and personalized role design and allocation by players is enabled by exploring local smart objects as game props. The variability of the game is also enhanced by several other aspects, such as user-oriented context-aware action setting and playing environment redeployment. The effectiveness of the “design-in-play” concept is validated through a user study, where 15 subjects were recruited to play and author the trial game.